Comparison of the amplitude of accommodation measured using a new-generation closed-field autorefractor with conventional subjective methods - Kanclerz, Piotr; Pluta, Karolina; Momeni-Moghaddam, Hamed; Khoramnia, Ramin (Diagnostics, 2022)
Purpose: This study aims to compare and assess the agreement of the objective amplitude of accommodation (AA) measured using a new-generation closed-field autorefractor with conventional subjective methods. Methods: In total, 84 healthy individuals with an age range of 19 to 50 years participated in this cross-sectional study. AA was measured objectively with a Nidek autorefractor (AR-1a; Nidek Co., Ltd., Tokyo, Japan) and subjectively using push-up (PU) and minus-lens (ML) methods in a random order. Comparison between different methods was performed using repeated-measures analysis of variance and the Bonferroni test for pairwise comparisons. In addition to the Pearson correlation, the Bland and Altman method and the intraclass correlation coefficient were used to determine the agreement between the three techniques. Only the right-eye results were used for analysis. Results: AA measured using the Nidek autorefractor (3.43 ± 1.94 D) was significantly lower than that measured with PU (7.67 ± 2.38 D; p < 0.001) and ML (7.60 ± 2.81 D; p < 0.001) methods. The difference between the subjective methods was not significant statistically (p = 1.0). The correlation for Nidek measurements and PU and ML methods was moderate (r = 0.5502 and r = 0.6832, respectively), while it was strong when comparing subjective methods (r = 0.7821). The limits of agreement for Nidek vs. PU, Nidek vs. ML, and PU vs. ML methods were −8.28 to −0.23 D, −8.19 to −0.15 D, and −3.38 to 3.51 D, respectively. Conclusions: There was a moderate agreement between AA obtained with subjective methods and objective Nidek measurements. The objective AA measurements obtained with a new Nidek autorefractor were significantly lower than subjective measurements.
Gesehen am 04.06.2022